440 Have We Made Temporal Advancements in Optimizing Surgical Outcomes and Recovery for High Risk Spinal Deformity Patients?. (1st April 2022) - Passias, Peter G.; Passfall, Lara; Lafage, Virginie; Lafage, Renaud; Line, Breton G.; Vira, Shaleen; Tretiakov, Peter S.; Gum, Jeffrey L.; Kebaish, Khaled; Than, Khoi D.; Mundis, Gregory M.; Hostin, Richard A.; et al.
Abstract : INTRODUCTION: Surgical correction of adult spinal deformity (ASD) has high rates of complication. However, patients often derive significant benefits in functional status and quality of life from surgery despite high-risk status. It has yet to be investigated whether spine surgeons are improving surgery for high risk patients and minimizing poor outcomes. METHODS: Included: operative ASD pts =18 yrs with pre-(BL) and 2-year (2Y) postop radiographic/HRQL data. Pts were categorized as having undergone surgery from 2009 to 2013[Early] or 2014 to 2018[Late]. High risk [HR] pts were defined as meeting =2 of the following BL criteria: 1) ++PILL or SVA by SRS-Schwab, 2) elderly [=70yrs], 3) severe frailty[Miller index], 4) high CCI [=1 SD above cohort mean], 5) three column osteotomy, and 6) fusion of >12 levels, or >7 levels for elderly pts. Differences in Smith et al. best/worst clinical outcomes, radiographic alignment targets(SRS-Schwab, age-adjusted, GAP score), and complication rates were assessed by time of surgery(Early/Late) for HR pts. RESULTS: 725 ASD pts included (61yrs, 77%F, CCI: 1.82±1.74, levels fused 11.0±4.4). 18.5% underwent 3CO. SRS-Schwab modifiers at BL: 41.4% ++PI-LL, 30.3% ++SVA, 28.8% ++PT. 47% of pts (n=338) had surgery prior to 2014[Early], and 53% (n=387) underwent surgery in 2014 or later[Late]. Overall, 52% of pts (n=377) were deemed high risk[HR]. There was a higher proportion of HR pts in the Late group (p=0.028). In terms of individual HR criteria: Late pts were older, more likely to be ++PI-LL at BL, had higher CCI, and were less likely to undergo 3CO (all p<0.05). Analysis of HR pts by Early/Late status showed no significant differences in radiographic alignment by SRS-Schwab, age-adjusted target, or GAP score by 2Y (all p>0.05). Late/HR pts were less likely to have a poor outcome by Smith et al. definition for SRS and ODI (both p<0.01). Late/HR pts had lower rates of complication, reoperation, deep surgical infection, early PJK (before 6 months), and PJF by 2Y (p<0.05). CONCLUSION: Over time in our data set, spine surgeons have both increased and optimized operating on high risk patients, while minimizing the occurrence of poor clinical outcomes and reducing complication rates.